2016
DOI: 10.1016/s2095-3119(15)61047-4
|View full text |Cite
|
Sign up to set email alerts
|

Slight shading after anthesis increases photosynthetic productivity and grain yield of winter wheat (Triticum aestivum L.) due to the delaying of leaf senescence

Abstract: The solar radiation intensity and duration are continuously decreasing in the major wheat planting area of China. As a consequence, leaf senescence, photosynthesis, grain filling and thus wheat yield shall be affected by light deficiency. Therefore, two winter wheat (Triticum aestivum L.) cultivars, Tainong18 (a large-spike cultivar) and Jinan17 (a multiple-spike cultivar), were subjected to shading during anthesis and maturity under field condition in 2010-2011 and 2011-2012. Under the slight shading treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
7
30
0
Order By: Relevance
“…The same results were obtained in wheat. Research of Xu et al showed that slight shade did not significantly affect photosynthetic product accumulation in wheat [34]. A study on sweet potato showed that slight shade has little effect on plant growth and photosynthesis, and even has some positive effects [35].…”
Section: Discussionmentioning
confidence: 97%
“…The same results were obtained in wheat. Research of Xu et al showed that slight shade did not significantly affect photosynthetic product accumulation in wheat [34]. A study on sweet potato showed that slight shade has little effect on plant growth and photosynthesis, and even has some positive effects [35].…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have shown that shading stress causes yield loss (Liu et al, 2015b;Xu et al, 2016). When grain number decreases, a limited supply from the source could have positive effects on grain weight.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, this was evident mainly after 1, 2, and 3 d of shading stress. Multiple studies have shown that shading stress causes yield loss (Liu et al, 2015b;Xu et al, 2016). This is mainly caused by reduction in grain number and grain weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations